Effects of the injection parameters and compression ratio on the emissions of a heavy-duty diesel engine - (:unkn) unknown (INDERSCIENCE ENTERPRISES LTD, 2012)
Homogenous charge compression ignition (HCCI) cases are compared for improvements on the combustion chamber design of the engine to achieve near zero particulate matter (PM) and NOx emissions. Therefore combustion simulations of the engine have been performed to find out emission generation in the cylinder. The interaction of air motion with high-pressure fuel spray has also been analyzed. Finally, a comparison has been made considering the performance of the engine for various configurations such as compression ratio, injection timing, and cone angle. The results are widely in agreement qualitatively with the previous similar experimental and computational studies in the literature.
Keywords: Clean Diesel Combustion; CFD; spray; injection parameters; narrow angle; combustion; emissions; combustion chamber; EXHAUST EMISSIONS; MODELS